The Role of Self-Discipline, Self-Concept and Self-Efficiency on Teacher Performance: self-discipline; self-concept; self-efficiency; teacher performance - Djazilan, Syukron; Darmawan, Didit; Retnowati, Eli; Sinambela, Ella Anastasya; Mardikaningsih, Rahayu; Issalillah, Fayola; Khayru, Rafadi Khan (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
The quality of education is very dependent on the role of teachers in it because teachers are professional educators. Quality education processes and outcomes are also inseparable from teacher performance. Therefore, given the importance of this, various efforts are still being made to improve teacher performance such as self-discipline, self-concept and self-efficacy as will be discussed in this study. This study uses a quantitative approach by using the method of observation and questionnaire design. The population observed was 38 teachers, because the number was less than 100, the sample was determined using the census technique. The data were then tested for validity and reliability as well as the classical assumption test. In the end there is multiple regression analysis using SPSS version 26.0 program. The conclusion that self-discipline has a significant effect on improving teacher performance. Likewise, what happened to the independent variables of self-concept and self-efficacy also had a partial and significant influence on improving teacher performance. These three variables have a significant effect simultaneously on improving teacher performance.